Enhanced machine learning techniques for microarray cancer classification - Shen, Li (2008)
This thesis deals with the problem of microarray cancer classification. Machine learning methods have been used and enhanced to tackle the task. Some novel use of the current methods has been presented. Evaluation based on classification accuracy and execution time has shown the advantages of the enhancements.